Pre-service Teachers’ Perceptions of TBLT and the Introduction of Rap Battles in Foreign Language (FL) Teaching - Noelia Mª Galán-Rodrígez (Acta Universitatis Sapientiae: Philologica)
The latest educational trends have put emphasis on a communicative approach to FL teaching and learning, focusing on meaning, functionality, and the integration of skills (Richards and Rodgers 2015) Therefore, it is necessary that FL teachers become acquainted with methodologies which follow an integrated-skills approach such as TBLT This article analyses pre-service teachers’ uptakes on TBLT and the use of rap battles in FL teaching in primary education through an exploratory analysis After having taken a one-week course on TBLT in a TEFL module, a questionnaire was given to participants Results show that pre-service teachers understand the importance of integrating all language skills in FL lessons for primary school students as well as the 4 Cs on learning and innovation skills (Partnership for 21st-Century Learning 2011) Furthermore, they report that rap battles are motivating and creative resources which could be exploited in FL lessons, although they also point out some challenges.